Amplatzer Amulet Left Atrial Appendage Occluder Versus Watchman Device for Stroke Prophylaxis (Amulet IDE): A Randomized, Controlled Trial. Issue 19 (9th November 2021) - Lakkireddy, Dhanunjaya; Thaler, David; Ellis, Christopher R.; Swarup, Vijendra; Sondergaard, Lars; Carroll, John; Gold, Michael R.; Hermiller, James; Diener, Hans-Christoph; Schmidt, Boris; MacDonald, Lee; Mansour, Moussa; et al.
Abstract : Background: Percutaneous closure of the left atrial appendage (LAA) is an alternative to chronic oral anticoagulation to reduce stroke risk in patients with nonvalvular atrial fibrillation. The Amulet IDE trial (Amplatzer Amulet Left Atrial Appendage Occluder IDE Trial) was designed to evaluate the safety and effectiveness of the dual-seal mechanism of the Amulet LAA occluder compared with the Watchman device. Methods: Patients with nonvalvular atrial fibrillation at increased risk of stroke were randomly assigned (1:1) to undergo percutaneous implantation of a LAA occluder with the Amulet occluder or Watchman device. The primary end points included safety (composite of procedure-related complications, all-cause death, or major bleeding at 12 months), effectiveness (composite of ischemic stroke or systemic embolism at 18 months), and the rate of LAA occlusion at 45 days. Prespecified secondary end points included a composite of all stroke, systemic embolism, or cardiovascular/unexplained death at 18 months, major bleeding at 18 months, and superiority test of the 3 primary end points. Results: A total of 1878 patients were enrolled. The Amulet occluder was noninferior to the Watchman device for the primary safety end point (14.5% versus 14.7%; difference=–0.14 [95% CI, –3.42 to 3.13]; P <0.001 for noninferiority). Major bleeding and all-cause death were similar between groups (10.6% versus 10.0% and 3.9% versus 5.1%, respectively). Procedure-related complications were higher for the Amulet occluder (4.5% versus 2.5%), largely related to more frequent pericardial effusion and device embolization. The Amulet occluder was noninferior to the Watchman device for the primary effectiveness end point (2.8% versus 2.8%; difference=0.00 [95% CI, –1.55 to 1.55]; P <0.001 for noninferiority), and the composite of stroke, systemic embolism, or cardiovascular/unexplained death (5.6% versus 7.7%, difference=–2.12 [95% CI, –4.45 to 0.21]; P <0.001 for noninferiority). The rate of major bleeding was similar between groups (11.6% versus 12.3%; difference=–0.71 [95% CI, –3.72 to 2.31]; P =0.32 for superiority). LAA occlusion was higher for the Amulet occluder than for the Watchman device (98.9% versus 96.8%; difference=2.03 [95% CI, 0.41–3.66]; P <0.001 for noninferiority; P =0.003 for superiority). Conclusions: The Amulet occluder was noninferior for safety and effectiveness of stroke prevention for nonvalvular atrial fibrillation compared with the Watchman device and superior for LAA occlusion. Procedure-related complications were higher with the Amulet occluder and decreased with operator experience. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02879448. Abstract : Supplemental Digital Content is available in the text.